SPICE modeling of nonlinear memristive behavior - Vourkas, Ioannis; Batsos, Athanasios; Sirakoulis, Georgios Ch (International journal of circuit theory and applications, 2015)
Summary The recent discovery of the ‘modern’ memristor has drawn great attention of both academia and industry. Given their favorable performance merits, memristors are expected to play a fundamental role in electronic industry. Modeling of memristive devices is essential for circuit design, and a number of Simulation Program with Integrated Circuit Emphasis (SPICE) models have already been introduced. The common problem in most models is that there is no threshold consideration; hence, only a few address the nonlinear nature of the device. This paper aims to present a SPICE implementation of a threshold‐type switching model of a voltage‐controlled memristive device that attributes the switching effect to a tunneling distance modulation. Threshold‐type switching is closer to the actual behavior of most experimentally realizable memristive systems, and our modeling approach addresses the issue of programming thresholds. Both the netlist and the simple schematic are provided, thus making it easy to comprehend and ready to be used. Compared with other modeling solutions, it involves significantly low‐complexity operation under an unlimited set of frequencies, and its simulation results are in good qualitative and quantitative agreement with the theoretical formulation. The proposed model is used to simulate an antiserial memristive switch, proving that it can be efficiently introduced in complex memristive circuits. Copyright © 2013 John Wiley & Sons, Ltd. This paper presents an easily adaptive SPICE implementation of a threshold‐type switching model of a voltage‐controlled memristive device. Compared with other solutions, it includes the concept of programming thresholds; it also has an unlimited set of working frequencies and its simple equations guarantee low‐complexity operation. The simulation results are in good qualitative and quantitative agreement with the theoretical formulation and its dynamic behavior clearly fulfills the memristive fingerprints.